Potter task in San Felipe Cuapexco, Puebla and its potential for value-added production - Deolarte George, Monica; Aguirre Álvarez Luciano; Jaramillo Villanueva José Luis; Escobedo Garrido José Sergio; Álvarez Gaxiola Jesús Felipe; Montalvo Paquini, Claudia (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to known the pottery work, to identify its troubles and start actions leading to improve the quality of this kind of craft (particularly the production of rustic (comales) in San Felipe Cuapexco, Puebla, this work applied elements of participatory action research in combination with some quantitative methods. With the consensus among participants it was conducted a teaching-learning process in order to appropriate the techniques to pasting stickers to the polyoleo and also by hand painting in acrylic on the rustic comales. During this process, the potters ‘willingness to work together as a team was increased, beside the communication and the assistance among them’. The craftsmen who produced throughout all the year and have the higher production capacity were the most active participants. It was found that an alternative to increase the griddles or comales value is through painting and decorating them, diversifying their use as decorative crafts items, expecting to earn up to four times in contrast with its regular price as rustic comales.